2021
DOI: 10.3390/s21020595
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Planning Approach Based on MPC and Parametric Curves for Overtaking Maneuvers

Abstract: Automated Driving Systems (ADS) have received a considerable amount of attention in the last few decades, as part of the Intelligent Transportation Systems (ITS) field. However, this technology still lacks total automation capacities while keeping driving comfort and safety under risky scenarios, for example, overtaking, obstacle avoidance, or lane changing. Consequently, this work presents a novel method to resolve the obstacle avoidance and overtaking problems named Hybrid Planning. This solution combines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, the proposed method does not consider acceleration and jerk, and it may create uncomfortable driving motions. Lattarulo and Pérez Rastelli 33 limited the range of longitudinal acceleration and jerk, and lateral acceleration to improve driving comfort. However, the proposed method only considers the minimization of path tracking error and speed error when planning motion.…”
Section: Related Workmentioning
confidence: 99%
“…However, the proposed method does not consider acceleration and jerk, and it may create uncomfortable driving motions. Lattarulo and Pérez Rastelli 33 limited the range of longitudinal acceleration and jerk, and lateral acceleration to improve driving comfort. However, the proposed method only considers the minimization of path tracking error and speed error when planning motion.…”
Section: Related Workmentioning
confidence: 99%
“…Describing the camera trajectory using continuous B-splines offers the advantage that any exposure time along the path can be interpolated and thus allows for correcting the rolling shutter for both monocular [24] and stereo (RGB-D) [20] cameras. To predict and plan the future paths for Automated Driving Systems (ADS), while taking into account obstacles and driving comfort, it was shown that Bézier curves are a reliable solution for an optimal trajectory generation [11,21].…”
Section: Engineering Purpose and Related Workmentioning
confidence: 99%
“…This short review of interdisciplinary research contains many different types of spline representation, such as Bézier [7,11,21], Catmull-Rom [8], B-Splines [20,24] and Non-uniform Rational B-Spline (NURBS) [12] surfaces. This shows the relevance of providing conversion methods between the various representations of which one is discussed in this paper.…”
Section: Engineering Purpose and Related Workmentioning
confidence: 99%
“…As an unmanned operational intelligence capable of multiple functions, Unmanned Aerial Vehicles (UAVs) are widely used in military and civilian applications due to their low cost, ease of integration and modular design [1][2][3][4][5]. UAVs formations are gradually replacing single UAV in complex missions due to their greater endurance and ability to handle complex missions compared to single UAV.…”
Section: Introductionmentioning
confidence: 99%